Maps of African American and White Populations in 100 Metro Areas - (:unkn) unknown (My University, 2002)
The Employment and Training Institute prepared maps for the 100 largest metro areas in the U.S. to aid public policy makers in identifying black-white integrated neighborhoods. The mapping project analyzed block level data, with cities encouraged to map their integrated neighborhoods by blocks. For ease of display, the metro maps shown here use block groups to aid communities in assessing the location and relative size of their racial mixes. Four maps are provided for each metro area. The first map shows the black-white racial composition by three categories: integrated block groups with at least 20 percent black population and at least 20 percent white population, block groups that are over 80 percent black, and block groups that are over 80 percent white. Concentrations of population are based on density per square mile. As a result, urban neighborhoods with highest concentrations of residents (in integrated, predominantly black, or predominantly white block groups) are tallest in the 3-D maps presented, while sparsely populated areas appear flat. Block groups are excluded where the institutionalized population makes up more than a third of the total population or where the block group population totals less than 50 people. Some metropolitan areas have residents living on black-white integrated blocks but have no block groups meeting the black-white integration criteria. Likewise, some metro areas, particularly those with large Latino and Asian populations, may show no blocks groups where the population is over 80 percent black or over 80 percent white.
Keywords: housing segregation; housing integration; African Americans